A fluorescent lateral flow immunoassay based on CdSe/CdS/ZnS quantum dots for sensitive detection of olaquindox in feedstuff. (1st September 2023) - Hu, Mei; Hu, Xiaofei; Wang, Guoqiang; Cheng, Yongxia; Yu, Xiaoling; Huang, Xianqing; Li, Yu
Graphical abstract: Highlights: A novel bioprobe was prepared based on the CdSe/CdS/ZnS quantum dots. The fluorescent lateral flow immunoassay was constructed for OLA detection. A detection limit of 0.12 μg/kg was obtained. The QDs-LFIA could be built in the food safety fields of target assays by replacing the mAbs. Abstract: A portable fluorescence immunosensor based on the CdSe/CdS/ZnS quantum dots (QDs) with multiple-shell structure was fabricated for the precise quantification of olaquindox (OLA). The QDs labeled anti-OLA antibody used as bioprobe played an important role in the design and preparation of a lateral flow test strip. Due to the strong fluorescent intensity of QDs, the sensitivity is greatly improved. The quantitative results were obtained using a fluorescent strip scan reader within 8 min, and the calculated limit of detection for OLA at 0.12 µg/kg, which was 2.7 times more sensitive than that of the conventional colloidal gold-based strips method. Acceptable recovery of 85.0%-95.5% was obtained by the spiked samples. This newly established QDs-based strip immunoassay method is suitable for the on-site detection and rapid initial screening of OLA in swine feedstuff, and is potentially applied for the detection of other veterinary drugs to ensure food safety.